On weighted Calderon-Zygmund singular integrals and applications - Loulit, Ahmed (Journal of Innovative Applied Mathematics and Computational Sciences, 2022)
This paper studies some weighted norm inequalities related to some Calderon-Zygmund singular integrals. Applications to the Sobolev-Gagliardo-Nirenberg inequality, differential forms, and the potential equation du= f are given.